Temporal progression of anaerobic fungal communities in dairy calves from birth to maturity - Jones, Adrienne L.; Clayborn, Jordan; Pribil, Elizabeth; Foote, Andrew P.; Montogomery, Dagan; Elshahed, Mostafa S.; Youssef, Noha H. (Environmental microbiology, 2023)
Establishment of microbial communities in neonatal calves is vital for their growth and overall health. While this process has received considerable attention for bacteria, our knowledge on temporal progression of anaerobic gut fungi (AGF) in calves is lacking. Here, we examined AGF communities in faecal samples from six dairy cattle collected at 24 different time points during the pre‐weaning (days 1–48), weaning (days 48–60), and post‐weaning (days 60–360) phases. Quantitative polymerase chain reaction indicated that AGF colonisation occurs within 24 h after birth, with loads slowly increasing during pre‐weaning and weaning, then drastically increasing post‐weaning. Culture‐independent amplicon surveys identified higher alpha diversity during pre‐weaning/weaning, compared to post‐weaning. AGF community structure underwent a drastic shift post‐weaning, from a community enriched in genera commonly encountered in hindgut fermenters to one enriched in genera commonly encountered in adult ruminants. Comparison of AGF community between calves day 1 post‐birth and their mothers suggest a major role for maternal transmission, with additional input from cohabitating subjects. This distinct pattern of AGF progression could best be understood in‐light of their narrower niche preferences, metabolic specialisation, and physiological optima compared to bacteria, hence eliciting a unique response to changes in feeding pattern and associated structural GIT development during maturation.